Tingkat Keterampilan Dasar Pencak Silat Pada Peserta Ekstrakurikuler Pencak Silat Muhammadiyah 1 Medan Tahun 2022 - Ardianti Rizki Putri; Devi Catur Winata; Filli Azandy (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research was conducted in the field of SMP Muhammadiyah 1 Medan in August 2022. This study aims to determine the level of basic skills of pencak silat students participating in pencak silat extracurricular at SMP Muhammadiyah 1 Medan. The method used in this research is a survey with test and measurement techniques. The subjects of this study were students who participated in extracurricular pencak silat at SMP Muhammadiyah 1 Medan, totaling 16 boys/girls. The results showed that the level of basic skills of pencak silat extracurricular students of SMP Muhammadiyah 1 Medan 0 students (0%) in the very good category, 0 students (0%) in the good category, 0 students (0%) in the medium category, 14 (87,5%) students in the poor category, and 2 student (12,5%) in the Medium category. So it can be concluded that the basic skill level of pencak silat in Pencak silat extracurricular participants at SMP Muhammadiyah 1 Medan in 2022 is in the Medium category, this triggers many things, one of which is a lack of training and the training program that has been prepared has not been fully carried out properly.